KEWENANGAN PEMERINTAH DALAM OTONOMI DAERAH DAN OMNIBUS LAW CIPTA KERJA (Solusi, 2022)
Law Number 11 of 2020 concerning Job Creation is an effort to create jobs through efforts to protect the empowerment of cooperatives and micro, small and medium enterprises, improve the investment ecosystem and facilitate the central government's investment business and accelerate national strategy projects as a breakthrough in our legal system in the formation of laws and regulations, especially related to regional autonomy, the form of regional autonomy provides regional independence as a region that is able to manage regulations for accelerating development. However, the Omnibus Law is very much against regional autonomy, including in the licensing system and some regional authorities are taken by the central government. For this reason, it is necessary to immediately make changes and adjustments to the concept of regional autonomy as regulated in the Indonesian constitution so that there is harmony in the regulation and implementation of development related to the position of the governor as regional head. The presence of the Omnibus Law on Job Creation, which has been ratified by the House of Representatives and officially applies in Indonesia, is a hope that is believed to be a strategy and hope in realizing simple, clean, and transparent public services so that it can encourage higher economic growth and investment and can create more new jobs and take advantage of local wisdom to overcome unemployment in the region.